2015
DOI: 10.1158/1055-9965.epi-14-0980
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine, Phenylalanine, and Tryptophan in Gastroesophageal Malignancy: A Systematic Review

Abstract: Gastroesophageal cancer has a rapidly increasing incidence worldwide and reliable biomarkers are urgently required to facilitate earlier diagnosis and improve survival. The aromatic amino acids tyrosine, phenylalanine, and tryptophan represent potential biomarkers and their relation to gastroesophageal cancer will be evaluated in this review. An electronic literature search was performed to identify all published research relating to the measurement of tyrosine, phenylalanine, or tryptophan in the biofluids or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 35 publications
4
72
0
Order By: Relevance
“…In recent studies of tumor metabolomics, various amino acids have been demonstrated to be helpful for the study of potential biomarkers and pathogenesis of diverse malignancies (22). It has been found that alterations in amino acid metabolic profile show a correlation with GC, and the metabolic pathways of amino acids are abnormal in patients with GC (23,24) the levels of plasma aromatic amino acids, including tyrosine, phenylalanine and tryptophan, decreased overall in GC patients (25). Miyagi et al observed that citrulline, valine, tryptophan and histidine levels were significantly lower in GC patient plasma, whereas isoleucine and lysine were higher (26).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies of tumor metabolomics, various amino acids have been demonstrated to be helpful for the study of potential biomarkers and pathogenesis of diverse malignancies (22). It has been found that alterations in amino acid metabolic profile show a correlation with GC, and the metabolic pathways of amino acids are abnormal in patients with GC (23,24) the levels of plasma aromatic amino acids, including tyrosine, phenylalanine and tryptophan, decreased overall in GC patients (25). Miyagi et al observed that citrulline, valine, tryptophan and histidine levels were significantly lower in GC patient plasma, whereas isoleucine and lysine were higher (26).…”
Section: Discussionmentioning
confidence: 99%
“…Lactate, threonine, acetate, uracil, succinate, lysine and tyrosine, myo-inositol, taurine and creatine have been shown to be associated with the presence of rectal cancer, and correlated with its progression (79). Taurine is also increased in squamous-cell carcinoma (80), while lactate has additionally been shown to be associated with oesophago-gastric cancer (81), along with fumurate, valine, glutamine, glutamate (81), xylonic acid (81, 82), tyrosine, phenylalanine, and tryptophan (83). Together these metabolites indicate a general dysregulation in the metabolism of cellular respiration, energy, amino acids, ketone body and choline metabolism which, as discussed, could be applicable to all cancers.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The increases in Phe and Tyr in the urine of 5p− patients reflect disturbances in Phe metabolism and an imbalance in food products rich in Phe, an essential amino acid to the body and a precursor to Tyr, by action of Tyr hydroxylase enzyme (Wiggins, Kumar, Markar, Antonowicz, & Hanna, ). High concentrations of Phe are shown in phenylketonuric patients owing to hydroxylase Phe enzyme (EC: 1.14.16.1) failure (Zschocke, ).…”
Section: Discussionmentioning
confidence: 99%